2016
DOI: 10.1093/pm/pnw243
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Radiofrequency Attenuates Complete Freund’s Adjuvant–Induced Epigenetic Suppression of Potassium Chloride Cotransporter 2 Expression

Abstract: These findings suggest that PRF might be an alternative therapy for inflammatory pain. One of the underlying mechanisms is through modification of KCC2, which is an important determinant for the efficacy of inhibitory neurotransmission in the spinal cord, and its expression levels are regulated by histone acetylation epigenetically following inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recent studies have found that PRF can produce neuromodulation and relieve trigeminal PHN (Ding et al, 2019). It has been found that PRF can inhibit the nociceptive-induced release of excitatory neurotransmitters (Huang et al, 2016), reduce the expression of calcitonin gene-related peptide (CGRP) in DRG (Ren et al, 2018), inhibit the expression of P2 × 3 receptor in DRG and spinal dorsal horn (Fu et al, 2019), and reduce the expression of peripheral of pro-inflammatory cytokines (TNF-α and IL-6) and β-Catenin in spinal cord (Vallejo et al, 2013;Jiang et al, 2019); At the same time, PRF can up-regulate GDNF transcription and translation (Jia et al, 2016;Hailong et al, 2018), up-regulate GABAB-R1, Na/K ATPase and 5-HT3r gene expression (Vallejo et al, 2013), increase histone acetylation and KCC2 expression by modifying KCC2 and partially restored GABA synaptic function (Liu et al, 2017). The effect of neuromodulation is slow, so cervical nerve root PRF combined with nerve block was used.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that PRF can produce neuromodulation and relieve trigeminal PHN (Ding et al, 2019). It has been found that PRF can inhibit the nociceptive-induced release of excitatory neurotransmitters (Huang et al, 2016), reduce the expression of calcitonin gene-related peptide (CGRP) in DRG (Ren et al, 2018), inhibit the expression of P2 × 3 receptor in DRG and spinal dorsal horn (Fu et al, 2019), and reduce the expression of peripheral of pro-inflammatory cytokines (TNF-α and IL-6) and β-Catenin in spinal cord (Vallejo et al, 2013;Jiang et al, 2019); At the same time, PRF can up-regulate GDNF transcription and translation (Jia et al, 2016;Hailong et al, 2018), up-regulate GABAB-R1, Na/K ATPase and 5-HT3r gene expression (Vallejo et al, 2013), increase histone acetylation and KCC2 expression by modifying KCC2 and partially restored GABA synaptic function (Liu et al, 2017). The effect of neuromodulation is slow, so cervical nerve root PRF combined with nerve block was used.…”
Section: Discussionmentioning
confidence: 99%
“…PRF inhibited the excitatory neurotransmitter (glutamate) induced by nociception and then induced an analgesic effect on neuropathic pain (Huang et al, 2016). PRF increased histone acetylation and potassium-chloride cotransporter 2 (KCC2) expression, partially restored GABA synaptic function, alleviated inflammatory pain sensitization (Liu et al, 2017), and attenuated JNK activation in the spinal dorsal horn (Chen et al, 2014). Therefore, PRF effectively relieves pain, and can be maintained over an extended period of time.…”
Section: Discussionmentioning
confidence: 99%
“…100,101 In addition, epigenetic modification of KCC2 gene expression modulated by histone acetylation affects efficacy of GABAergic inhibitory neurotransmission in the spinal dorsal horn. 102 GABAergic plasticity: A potential target for neuropathic pain treatment…”
Section: Epigenetic Etiologies Of Gabaergic Plasticity In Neuropathic Painmentioning
confidence: 99%